Durability of adhesively bonded joints between pultruded GFRP adherends under hygrothermal and natural ageing. (1st February 2019) - Sousa, J.M.; Correia, J.R.; Gonilha, J.; Cabral-Fonseca, S.; Firmo, J.P.; Keller, T.
Abstract: This paper presents an experimental and numerical study about the durability of adhesively bonded joints between pultruded glass fibre reinforced polymer (GFRP) adherends for civil engineering applications. Single lap joint (SLJ) specimens were manufactured using either epoxy (EP) or polyurethane (PUR) adhesives and exposed to the following hygrothermal and outdoor ageing conditions for up to 730 days: water and salt water immersion at 20 °C and 40 °C, continuous condensation at 40 °C, salt fog spray at 35 °C, and outdoor ageing in Lisbon, Portugal. At predetermined times, the mechanical behaviour of the SLJs was assessed through shear tests, after drying the specimens to constant mass. Results obtained show that hygrothermal ageing detrimentally affected the failure load and stiffness of the SLJs made with both adhesives, although this degradation was balanced to some extent by post-curing effects and the desorption period (recovery after drying). The magnitude of such degradation was not significantly influenced by the immersion media, but was largely affected by temperature. Outdoor ageing did not cause significant changes in terms of stiffness; for both adhesives, failure load presented a moderate increasing trend, with cyclic pattern, reflecting the effects of seasonal changes in weather. For both adhesives, failure always initiated in one of the GFRP adherends, regardless of the ageing process. However, ageing seemed to affect the portion of bond area with either (light) fibre-tear or adhesive failure: in EP-GFRP specimens, the area with adhesive failure (initially null) increased due to ageing, while in PUR-GFRP specimens (significant in unaged joints) it decreased. The final part of the paper presents linear finite element (FE) models of the SLJs exposed to the harsher ageing environment; these models were developed to numerically simulate the mechanical performance of the joints and to assess the evolution of the internal stresses developed in the SLJs due to the effects of hygrothermal ageing in the constituent materials.